The Global Trail of Service: Strengthening Identity of Lampung through Local Products (Case Study: Banana Chips Industry) - Marisa Triana Mazta; Anggi Mega Rizki; Aliya Mutiara Yasmin; Enes Triyani; Rindu Rika Gamayuni; Retno Yuni Nur Susilowati (Indonesian Journal of Community Engagement, 2025)
This study examines how Lampung’s local product; banana chips can strengthen regional identity through global service interactions, using a community engagement activity conducted at Baiwang Company, Beijing, China, as a case study. As global markets increasingly value authenticity and culturally embedded products, this initiative explores the role of service encounters, product storytelling, and cross-cultural exchange in promoting local commodities at the international level. Using a qualitative descriptive approach supported by presentations, sensory testing, field observation, and stakeholder discussions, the study identifies key factors influencing the global acceptance of Lampung banana chips, including product quality, packaging durability, certification readiness, and cultural branding. The results show that Baiwang staff responded positively to the taste, uniqueness, and cultural narrative of the product, while also providing valuable insights into market preferences and regulatory requirements in China. The engagement demonstrates that service-based interactions significantly enhance product visibility and create pathways for international collaboration, including trial export opportunities and co-branded promotional activities. The findings conclude that strengthening local product identity in global markets requires integrated efforts among MSME actors, academic institutions, and international partners. This study contributes to broader discussions on global service trails, regional branding, and the internationalization of Indonesian MSMEs, positioning Lampung as a culturally distinctive region within the global supply chain.